DataGramaZero Vol. 13, n. 5 (2012) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
DataGramaZero Vol. 13, n. 5 (2012)Link de acesso ao númerohttp://www.datagramazero.org.br/out12/F_I_art.htm